2016
DOI: 10.1259/dmfr.20150327
|View full text |Cite
|
Sign up to set email alerts
|

The nasal septum deviation index (NSDI) based on CBCT data

Abstract: Objective: To assess whether three-dimensional morphometric parameters could be useful in nasal septal deviation (NSD) diagnosis and, secondarily, whether CBCT could be considered an adequate imaging technique for the proposed task. Methods: We analysed images of 46 subjects who underwent CBCT for reasons not related to this study. Two experienced operators divided all the images into healthy and NSD subjects. Subsequently, the images were segmented using ITK Snap in order to obtain the three-dimensional model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…The area of interest included the frontal sinuses at their respective ostium into the nasal cavities. Repeatability of the procedure of segmentation involving air spaces through a semi-automatic approach has already been verified by a previous publication [14]. Frontal sinuses from each individual were segmented twice from the same CT scan, in order to simulate AM and PM data for a possible matching procedure, and the respective models were included into two samples (named 1 and 2).…”
Section: Methodsmentioning
confidence: 85%
“…The area of interest included the frontal sinuses at their respective ostium into the nasal cavities. Repeatability of the procedure of segmentation involving air spaces through a semi-automatic approach has already been verified by a previous publication [14]. Frontal sinuses from each individual were segmented twice from the same CT scan, in order to simulate AM and PM data for a possible matching procedure, and the respective models were included into two samples (named 1 and 2).…”
Section: Methodsmentioning
confidence: 85%
“…Another study conducted using CT on the Iraqi population also reported mean SDA values as reported in the present study [ 21 ]. However, in a study by conducted by Codari M et al in the Italian population, the mean SDA was 17.3 degrees [ 22 ]. Another CT-based study conducted in the Iranian population also reported of lower mean SDA values compared to the present study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The several diagnostic methods currently used to investigate the NSD and MSMT 7,17 . The introduction of the CBCT provided the possibility of detecting anatomical abnormalities and pathologic areas within the nasal cavity and paranasal sinuses surrounding them for dentists and ENT specialists.…”
Section: Introductionmentioning
confidence: 99%